A week-end off: the first extensive number-theoretical computation on the ENIAC - De Mol, Liesbeth; Bullynck, Maarten (Logic and Theory of Algorithms, 2008)
The first extensive number-theoretical computation run on the ENIAC, is reconstructed. The problem, computing the exponent of 2 modulo a prime, was set up on the ENIAC during a week-end in July 1946 by the number-theorist D.H. Lehmer, with help from his wife Emma and John Mauchly. Important aspects of the ENIAC's design are presented-and the reconstruction of the implementation of the problem on the ENIAC is discussed in its salient points.